2022
DOI: 10.3390/ma15124250
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of Cement Stabilized Soil Incorporating Solid Waste and Propylene Fiber

Abstract: Cement stabilized soil (CSS) yields wide application as a routine cementitious material due to cost-effectiveness. However, the mechanical strength of CSS impedes development. This research assesses the feasible combined enhancement of unconfined compressive strength (UCS) and flexural strength (FS) of construction and demolition (C&D) waste, polypropylene fiber, and sodium sulfate. Moreover, machine learning (ML) techniques including Back Propagation Neural Network (BPNN) and Random Forest (FR) were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Himouri et al [24] showed that the anti-drying shrinkage, mechanical strength and water absorption performance of stabilized soil improved with Date Palm fibers and cement were better than those of solely using cement. The above study found that the mechanical properties of cement-stabilized soil incorporated with fibers were enhanced [19][20][21][22][23][24]. In addition, in some research, the strength deterioration of cement-stabilized soil reinforced with fibers was reduced, and the durability was enhanced [5,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Himouri et al [24] showed that the anti-drying shrinkage, mechanical strength and water absorption performance of stabilized soil improved with Date Palm fibers and cement were better than those of solely using cement. The above study found that the mechanical properties of cement-stabilized soil incorporated with fibers were enhanced [19][20][21][22][23][24]. In addition, in some research, the strength deterioration of cement-stabilized soil reinforced with fibers was reduced, and the durability was enhanced [5,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 81%
“…Thus, some researchers have synergistically used fibers and inorganic stabilized agents to treat river silt. Zhang et al [19,20], Munoz et al [21], Sahlabadi et al [22] and Lu et al [23] found that the mechanical properties of cement-stabilized soil incorporating fibers were improved compared with using cement alone. Himouri et al [24] showed that the anti-drying shrinkage, mechanical strength and water absorption performance of stabilized soil improved with Date Palm fibers and cement were better than those of solely using cement.…”
Section: Introductionmentioning
confidence: 99%
“…Through the analysis of the prediction accuracy, stability, and parameter sensitivity of the optimal model, the prediction performance of the machine learning model for salinized frozen soil UCS driven by the three-level characteristic parameters is explored to provide a new reference for further improving the prediction ability of a model for UCS. [39] Note: R: Pearson's correlation coefficient; R 2 : determination coefficient; RMSE: root mean square error; MSE: mean square error; BP: back-propagation; REG: multiple linear regression; RDF: random decision forest; BLR: Bayesian linear regressor; XGB: extreme gradient boosting; KNN: k-nearest neighbor; RF: random forest; TCEF Soils: soils treated with calcium-based additives blended with eco-friendly pozzolans; GB-ML: machine learning using the gradient boosting; Australia-EBCA-Soils: earth building sites in Canberra, Australia; GB-PSO: gradient boosting machines-particle swarm optimizer; CPF Soils: cement stabilized soil incorporating solid waste and propylene fiber; BAS-BP: beetle antennae search BP.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, many researchers have investigated materials suitable for replacing natural aggregates with concrete [ 1 , 2 ]. The most commonly used methods involve crushed waste tires [ 3 ], crushed abandoned concrete [ 4 ], and sea sand [ 5 ].…”
Section: Introductionmentioning
confidence: 99%